Local a Priori and a Posteriori Error Estimate of TQC9 Element for the Biharmonic Equation (Journal of Computational Mathematics, 2018)
In this paper, local a priori, local a posteriori and global a posteriori error estimates are obtained for TQC9 element for the biharmonic equation. An adaptive algorithm is given based on the a posteriori error estimates.
Keywords: Finite element; Biharmonic equation; A priori error estimate; A posteriori error estimate; TQC9 element.